The Consequences of a Life in Scholarly Publishing - Philipson, Morris (Journal of Scholarly Publishing, 2013)
There is a set of values and goals that endures in scholarly publishing through the vagaries of format innovations, changing market conditions, and shifting intellectual fashions: a commitment to the idea of ideas; dedication to the essentials of communication, even at the price of hiding our part as publishers in the equation; and an appreciation of the power of transforming thought. As scholarly publishers, we nurture the ‘play’ of thought that is the life of the mind, and, in turn, in becoming what we do, we are the better for it.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDQuMi4wMDg